ANALISIS YURIDIS PENETAPAN TERSANGKA PEMBERI KETERANGAN PALSU DI BAWAH SUMPAH DI DEPAN PERSIDANGAN OLEH KOMISI PEMBERANTASAN KORUPSI TERHADAP SAKSI DALAM KASUS KORUPSI - Munte, Immanuel; ', Firdaus; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Basically, the Corruption Eradication Commission has the duty, authorityand obligation to conduct investigations, investigations, and prosecutions againstcorruption. One of the basis for arriving at the suspicion of false information isstated in Article 163 of the Criminal Procedure Code, from the formulation of thearticle it is known that one of the grounds for arriving at a false testimony is if thewitness's testimony in the hearing is different from the statement contained in theminutes. The judge has the right to assess the evidence of witness testimony andthe authority of the judge because of his position to determine witnesses whoallegedly gave false information in order to be processed in accordance withArticle 174 of the Criminal Procedure Code. The purpose of writing this scheme,namely; First, to find out the investigators of the Corruption EradicationCommission are authorized to determine the suspect providing false informationto witnesses who testify under oath before a court in a corruption case without acourt order. Second, to find out the arrangement or mechanism for determiningsuspects giving false information to witnesses who give testimony under oathbefore a court in a case of corruption based on the Criminal Procedure Code.This type of research can be classified in the type of normative juridicalresearch, because in this study the author conducted a study of the rules andregulations concerning the problem under study.From the results of the research problem there are two main things that canbe concluded. First, the Investigator of the Corruption Eradication Commissionhas the authority to determine the suspect giving false information to witnesseswho testify under oath before a court in a case of corruption without a court orderconstituting a mistake in law enforcement. Second, the arrangement ormechanism for determining the suspect giving false information to witnesses whotestify under oath before a court in a case of corruption based on the CriminalProcedure Code must refer to the provisions of Article 174. The author'ssuggestion, First, It is expected that there is legal certainty as efforts to overcomedifferences in law enforcement against witnesses who commit criminal acts beforea court hearing, judges and investigators must have clear and written limitationsin the legislation. Secondly, it is recommended that investigators respect theexamination process at a court of law not to investigate cases that are beingprocessed in court without any request or order from the case handling judge.Keywords: Law Enforcement - Witness - False Testimony - CorruptionEradication Commission